The Organizational Commitment in the Company and Its Relationship With the Psychological Contract - Herrera, Juan; De Las Heras-Rosas, Carlos (Frontiers in Psychology, 2021)
Business organizations in their work environment, aspire to create a high level of performance and low levels of absenteeism and turnover. Organizational commitment is considered a key factor in achieving this objective, however, it can be conditioned by several factors, among which is the psychological contract. The literature has related the organizational commitment with the fulfillment of the psychological contract framing it as one of the explanatory variables. This work aims to investigate research trends on psychological contract and organizational commitment. For this purpose, bibliometric techniques and the software SciMAT have been used. 220 journal articles indexed in Web of Science (WoS) were analyzed. The findings indicate that the theme chosen for this review is valid. Based on the relationship between the two concepts, as the most recurrent themes, issues such as the sense of justice and the consequences of the violation of the psychological contract, normative commitment, HR management or job insecurity are addressed. However, in the last period analyzed (2015–2018), publications related to more sensitive topics to the present time emerge, such as the employability or the impact of these two concepts in the new generations (millennial and generation-Y) or the retention of talent. On the other hand, shortcomings are detected in the research on the ideologically charged psychological contract, the analysis of the organizational context or cultural and demographic factors in relation to both theoretical constructs. The contribution of this work lies in giving visibility to scientific results, which will serve business organizations as instruments for decision making in their labor management and, for the scientific community, as knowledge of the research spaces to explore.